A critical analysis of the effects of measurements on international company scandals: The fraud act - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2012)
Following a series of global corporate scandals and the incidence of employees' fraudulent activities in the companies they work for over the two decades, the desire by stakeholders for more reliable information has increasingly become greater. Corporate scandals such as Enron, WorldCom, Vivendi, Royal Ahold, etc., which shook the corporate world to its very root as a result of some accounting irregularities, have weakened the trust and confidence of the public to a very high degree, whereas the concept of trust was supposed to be the basis on which international investment and economic development should be grounded (Gunn 2007). According to Chambers (2008), despite a series of measures which have since been taken, these scandals which were first reported in the media in the 2000s continue to hunt the corporate world. This was confirmed by the global mortgage crisis which originated in the USA in 2008 and was originally referred to as credit crisis, but eventually became a global financial crisis. © 2012 Springer-Verlag Berlin Heidelberg. All rights are reserved.